Flame-retardant laminated kraft paper and preparation method thereof
By using a mixed beating technology of flame-retardant wood pulp fiber and bleached needle wood pulp fiber in pressed kraft paper, combined with boric acid-modified silicon sol and magnesium-aluminum hydrotalcite combination, the problem of flammability of pressed kraft paper is solved, significantly improving the Its flame retardant performance meets the safety requirements of circuit board production.
Patent Information
- Application Number
- CN202411444150.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-07
AI Technical Summary
Compressed kraft paper is flammable when producing circuit boards and is not flame retardant, resulting in an increase in fire risk.
Using a mixed beating technology of flame-retardant wood pulp fiber and bleached needle wood pulp fiber, combined with boric acid-modified silicon sol and magnesium-aluminum hydrotalcite, fibers are oxidized through tetramethylpiperidine nitrogen oxide, sodium chlorite and sodium hypochlorite systems. The carbon dioxide forms flame retardant cellulose and is compounded with ammonium phosphate and magnesium aluminum hydrotalcite to form paper with good flame retardant effect.
It significantly improves the flame retardant performance of pressed kraft paper, extends combustion time, reduces the length of carbonization, meets the performance indicators of flame retardant paper, and ensures the safety of circuit board production.
Smart Images

Figure BDA0005087223010000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pressed kraft paper, in particular to flame-retardant pressed kraft paper and a preparation method thereof. Background Art
[0002] Kraft paper is a high-strength roll paper or flat paper made from kraft softwood pulp through pulping, papermaking and other steps. It is usually yellow-brown in color. It has good burst resistance and high tensile strength, and is widely used in chemical, machinery and other industries. Pressed kraft paper is an excellent cushioning material used in the production of flexible circuit boards, printed circuit boards and other circuit board industries. It can maintain relatively stable performance during high-temperature hot pressing, and the kraft paper itself has a certain degree of elasticity and cleanliness, ensuring that the circuit board will not be crushed or polluted during use. However, due to the influence of the nature of the raw materials, kraft paper itself is flammable and can easily become an ignition for fire. Therefore, the development of pressed kraft paper with good flame retardant effect has an important impact on the circuit board industry. Summary of the invention
[0003] The object of the present invention is to provide a flame retardant pressed kraft paper and a preparation method thereof, so as to solve the problem that the pressed kraft paper used in the production of circuit boards is flammable and has poor flame retardancy.
[0004] To achieve the above object, the present invention provides the following technical solutions:
[0005] A method for preparing flame-retardant pressed kraft paper, the preparation method comprising:
[0006] The flame retardant wood pulp fiber and the bleached coniferous wood pulp fiber are mixed, soaked and then beaten to obtain wood pulp slurry, the wood pulp slurry is dispersed and mixed with a retention aid and a flame retardant filler, stirred evenly, and paper sheets are obtained through papermaking, and boric acid-modified silica sol is coated on the paper sheets and dried to obtain flame retardant pressed kraft paper.
[0007] As a limitation of the present invention, the method for preparing the flame retardant wood pulp fiber is:
[0008] The bleached softwood pulp fiber is washed with ethanol and deionized water, and then dried to obtain pretreated pulp fiber, disodium hydrogen phosphate, sodium dihydrogen phosphate and deionized water are mixed to prepare a phosphate buffer, the phosphate buffer, the pretreated pulp fiber, tetramethylpiperidinium nitrogen oxide and sodium chlorite are evenly mixed, and the mixture is reacted at 55-65° C. and 50-70 rpm for 5-15 min, and after the reaction is completed, sodium hypochlorite is added to the reaction system, and the mixture is reacted at 55-65° C. and 50-70 rpm for 11-13 h, and after the reaction is completed, ethanol is added to terminate the reaction, and the fiber is taken out and washed with ethanol to obtain oxidized pulp fiber;
[0009] Aluminum trichloride and deionized water are mixed and stirred evenly to obtain an aluminum trichloride solution. Oxidized wood pulp fiber, ethanol and aluminum trichloride solution are mixed and reacted at 65-75°C for 1-3 hours. After the reaction is completed, the fiber is taken out, washed with deionized water, and dried at 55-65°C to obtain flame-retardant wood pulp fiber.
[0010] As a limitation of the present invention, the preparation method of the flame retardant filler is:
[0011] Mix ammonium carbonate and deionized water, stir evenly to obtain an ammonium carbonate solution, mix aluminum nitrate nonahydrate, magnesium nitrate hexahydrate, and deionized water, stir evenly, heat to 65-75° C., add the ammonium carbonate solution to the reaction system, react at 65-75° C. and 55-65 rpm for 1-3 hours, filter after the reaction, wash with deionized water, and dry at 85-95° C. for 10-14 hours to obtain a magnesium-aluminum hydrotalcite matrix;
[0012] Phosphoric acid is added into a reactor, and the phosphoric acid is stirred and heated at 25-35 rpm and a heating rate of 2-4°C / min, and the temperature is raised to 65-75°C, urea is added into the phosphoric acid, and the temperature is further raised to 120-140°C, and a magnesium-aluminum hydrotalcite matrix is added into the phosphoric acid, and the temperature is kept at 120-140°C for 15-25 minutes, and the temperature is raised to 165-175°C, and the phosphoric acid is cured for 1.5-2.5 hours, cooled, and crushed to obtain a flame retardant filler.
[0013] As a limitation of the present invention, the preparation method of the boric acid modified silica sol is:
[0014] Mix tetraethyl orthosilicate and ethanol, stir evenly to obtain tetraethyl orthosilicate alcohol solution, add boric acid to the tetraethyl orthosilicate alcohol solution, and adjust the pH of the tetraethyl orthosilicate alcohol solution to 1-3 with hydrochloric acid, react at 65-75°C and 90-110rpm for 2-4h, heat to 75-85°C, continue to react for 0.5-1.5h, and obtain boric acid modified silica sol.
[0015] As a limitation of the present invention, the mass ratio of the flame retardant wood pulp fiber to the bleached coniferous wood pulp fiber is (0.8-1.2):(3.6-4.4).
[0016] As a limitation of the present invention, the mass ratio of the wood pulp slurry to the retention aid and the flame retardant filler is (48-52):(0.8-1.2):(4.8-5.2).
[0017] As a limitation of the present invention, the oxidized wood pulp fiber raw material includes, by mass, 95 to 115 parts of phosphate buffer, 0.8 to 1.2 parts of pretreated wood pulp fibers, 0.03 to 0.05 parts of tetramethylpiperidinium nitrogen oxide, 1.72 to 1.74 parts of sodium chlorite, and 0.8 to 1.2 parts of sodium hypochlorite.
[0018] As a limitation of the present invention, the mass ratio of the oxidized wood pulp fiber, ethanol, and aluminum chloride solution is (1.8-2.2):(35-45):(18-22).
[0019] As a limitation of the present invention, the mass ratio of the phosphoric acid, urea and magnesium aluminum hydrotalcite matrix is (9.6-10.0):(10.6-11.0):(1.5-2.5).
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The primary hydroxyl groups on the cellulose molecular chain are oxidized to carboxyl groups using a tetramethylpiperidinium nitrogen oxide / sodium chlorite / sodium hypochlorite system, and then chelated with trivalent aluminum ions to obtain flame-retardant cellulose. During combustion, the carboxyl groups and hydroxyl groups on the flame-retardant cellulose molecular chain will dehydrate and combine to form cyclic lactide, and the trivalent metal ions will form an alkaline environment, promoting the decarboxylation reaction of the carboxyl groups to generate carbon dioxide and metal hydroxide, which will hinder further combustion.
[0022] The ammonium polyphosphate generated by the reaction of phosphoric acid and urea is compounded with magnesium aluminum hydrotalcite prepared with ammonium carbonate, aluminum nitrate nonahydrate, and magnesium nitrate hexahydrate, so that the ammonium polyphosphate can be evenly dispersed on the surface and interlayers of the magnesium aluminum hydrotalcite, and the solubility of the ammonium polyphosphate in water is reduced by forming chemical bonds, so that more of the ammonium polyphosphate remains in the paper. In addition, magnesium aluminum hydrotalcite is a layered double metal hydroxide and also has a flame retardant function. After ammonium polyphosphate and magnesium aluminum hydrotalcite are compounded, they can have a better synergistic flame retardant effect.
[0023] The modified silica sol obtained by the reaction of tetraethyl orthosilicate and boric acid is resistant to high temperatures. After being coated on paper, the paper is not easily ignited. During combustion, the silicon dioxide balls generated by the silicon element in the modified silica sol will cover the carbon layer to prevent further combustion, while the boron element will further carbonize the carbon layer, making it stronger and more heat-resistant, thereby enhancing the flame retardant effect. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Bleached coniferous wood pulp fiber (whiteness 89) was provided by Dalian Yangrun, and tetramethylpiperidinium nitride (T819129), tetraethyl orthosilicate (T819505), and CPAM retention aid (P888714) were provided by Shanghai McLean.
[0026] Example 1: A flame retardant pressed kraft paper, prepared by:
[0027] Step 1: Preparation of Oxidized Wood Pulp Fiber
[0028] By mass, the bleached coniferous wood pulp fiber was washed with ethanol and deionized water and dried to obtain pretreated wood pulp fiber, 7.1 parts of disodium hydrogen phosphate, 6 parts of sodium dihydrogen phosphate and 86.9 parts of deionized water were mixed to prepare a phosphate buffer, 100 parts of phosphate buffer, 1 part of pretreated wood pulp fiber, 0.04 parts of tetramethylpiperidine nitrogen oxide, and 1.73 parts of sodium chlorite were mixed evenly, and reacted at 60°C and 60rpm for 10 minutes. After the reaction was completed, 1 part of sodium hypochlorite was added to the reaction system, and the reaction was carried out at 60°C for 12 hours. After the reaction was completed, 4.5 parts of ethanol were added to terminate the reaction, the fiber was taken out, and washed with ethanol to obtain oxidized wood pulp fiber.
[0029] Step 2: Prepare flame retardant wood pulp fibers
[0030] By mass, 1 part of aluminum chloride and 9 parts of deionized water were mixed and stirred evenly to obtain an aluminum chloride solution. 2 parts of oxidized wood pulp fiber, 40 parts of ethanol and 20 parts of aluminum chloride solution were mixed and reacted at 70°C for 2 hours. After the reaction was completed, the fiber was taken out, washed with deionized water and dried at 60°C to obtain flame retardant wood pulp fiber.
[0031] Step 3: Preparation of magnesium-aluminum hydrotalcite matrix
[0032] By mass, 10 parts of ammonium carbonate and 100 parts of deionized water were mixed and stirred to obtain an ammonium carbonate solution; 17 parts of aluminum nitrate nonahydrate, 14 parts of magnesium nitrate hexahydrate, and 100 parts of deionized water were mixed and stirred to obtain an ammonium carbonate solution; the mixture was heated to 70°C, 110 parts of ammonium carbonate solution were added to the reaction system, and the mixture was reacted at 70°C and 60rpm for 2h. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried at 90°C for 12h to obtain a magnesium-aluminum hydrotalcite matrix.
[0033] Step 4: Prepare the flame retardant filler
[0034] 9.8 parts of phosphoric acid were added into the reactor by mass, and the phosphoric acid was stirred and heated at 30 rpm and a heating rate of 2-3°C / min, and the temperature was raised to 70°C. 10.8 parts of urea were added to the phosphoric acid, and the temperature was continued to be raised to 130°C, and 2 parts of magnesium aluminum hydrotalcite matrix were added, and the temperature was kept at 130°C for 20 minutes, and the temperature was raised to 170°C, cured for 2 hours, cooled, and crushed to obtain a flame retardant filler.
[0035] Step 5: Preparation of boric acid modified silica sol
[0036] By mass, 10 parts of tetraethyl orthosilicate and 150 parts of ethanol were mixed and stirred to obtain tetraethyl orthosilicate alcohol solution, 2 parts of boric acid were added to 160 parts of tetraethyl orthosilicate alcohol solution, and the pH of the solution was adjusted to 2 with hydrochloric acid, and the reaction was carried out at 70°C and 100rpm for 3h, and the temperature was raised to 80°C and the reaction was continued for 1h to obtain boric acid-modified silica sol.
[0037] Step 6: Prepare flame retardant laminated kraft paper
[0038] By weight, 10 parts of flame retardant wood pulp fibers and 40 parts of bleached coniferous wood pulp fibers were mixed and soaked in 500 parts of deionized water for 6 hours. The soaked mixed wood pulp fibers and 3000 parts of deionized water were added to a pulper for thorough pulping for 1 hour to obtain wood pulp slurry. The wood pulp slurry was deflated by a fiber separator at a deflation speed of 1000 rpm for 10 minutes to obtain deflated wood pulp slurry. 50 parts of the deflated wood pulp slurry, 1 part of CPAM retention aid, and 5 parts of flame retardant filler were mixed and stirred evenly. The paper sheets were made by a sheeter. 30 parts of boric acid modified silica sol were coated on 120 parts of the made paper sheets, and the paper sheets were dried at 2.5 MPa and 60°C for 30 minutes to obtain flame retardant pressed kraft paper.
[0039] Example 2: A flame retardant pressed kraft paper, prepared by:
[0040] Step 1: Preparation of Oxidized Wood Pulp Fiber
[0041] By mass, the bleached coniferous wood pulp fiber was washed with ethanol and deionized water and then dried to obtain pretreated wood pulp fiber, 7.1 parts of disodium hydrogen phosphate, 6 parts of sodium dihydrogen phosphate and 86.9 parts of deionized water were mixed to prepare a phosphate buffer, 100 parts of phosphate buffer, 1 part of pretreated wood pulp fiber, 0.04 parts of tetramethylpiperidine nitrogen oxide and 1.73 parts of sodium chlorite were mixed evenly, and reacted at 60°C and 60rpm for 10 minutes. After the reaction was completed, 1 part of sodium hypochlorite was added to the reaction system, and the reaction was carried out at 60°C for 12 hours. After the reaction was completed, 4.5 parts of ethanol were added to terminate the reaction, the fiber was taken out, and washed with ethanol to obtain oxidized wood pulp fiber.
[0042] Step 2: Prepare flame retardant wood pulp fibers
[0043] By mass, 1 part of aluminum chloride and 9 parts of deionized water were mixed and stirred evenly to obtain an aluminum chloride solution. 2 parts of oxidized wood pulp fiber, 40 parts of ethanol and 20 parts of aluminum chloride solution were mixed and reacted at 70°C for 2 hours. After the reaction was completed, the fiber was taken out, washed with deionized water and dried at 60°C to obtain flame retardant wood pulp fiber.
[0044] Step 3: Preparation of magnesium-aluminum hydrotalcite matrix
[0045] By mass, 10 parts of ammonium carbonate and 100 parts of deionized water were mixed and stirred to obtain an ammonium carbonate solution; 17 parts of aluminum nitrate nonahydrate, 14 parts of magnesium nitrate hexahydrate, and 100 parts of deionized water were mixed and stirred to obtain an ammonium carbonate solution; the mixture was heated to 70°C, 110 parts of ammonium carbonate solution were added to the reaction system, and the mixture was reacted at 70°C and 60rpm for 2h. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried at 90°C for 12h to obtain a magnesium-aluminum hydrotalcite matrix.
[0046] Step 4: Prepare the flame retardant filler
[0047] 9.8 parts of phosphoric acid were added into the reactor by mass, and the phosphoric acid was stirred and heated at 30 rpm and a heating rate of 2-3°C / min, and the temperature was raised to 70°C. 10.8 parts of urea were added to the phosphoric acid, and the temperature was continued to be raised to 130°C, and 2 parts of magnesium aluminum hydrotalcite matrix were added, and the temperature was kept at 130°C for 20 minutes, and the temperature was raised to 170°C, cured for 2 hours, cooled, and crushed to obtain a flame retardant filler.
[0048] Step 5: Preparation of boric acid modified silica sol
[0049] By mass, 10 parts of tetraethyl orthosilicate and 150 parts of ethanol were mixed and stirred to obtain tetraethyl orthosilicate alcohol solution, 2 parts of boric acid were added to 160 parts of tetraethyl orthosilicate alcohol solution, and the pH of the solution was adjusted to 2 with hydrochloric acid, and the reaction was carried out at 70°C and 100rpm for 3h, and the temperature was raised to 80°C and the reaction was continued for 1h to obtain boric acid-modified silica sol.
[0050] Step 6: Prepare flame retardant laminated kraft paper
[0051] 8 parts of flame retardant wood pulp fiber and 40 parts of bleached coniferous wood pulp fiber were mixed by weight and soaked in 500 parts of deionized water for 6 hours. The soaked mixed wood pulp fibers and 3000 parts of deionized water were added to a pulper for thorough pulping for 1 hour to obtain wood pulp slurry. The wood pulp slurry was deflated by a fiber separator at a deflation speed of 1000 rpm for 10 minutes to obtain deflated wood pulp slurry. 48 parts of the deflated wood pulp slurry, 0.8 parts of CPAM retention aid and 4.8 parts of flame retardant filler were mixed and stirred evenly. The paper sheets were made by a sheeter. 30 parts of boric acid modified silica sol were coated on 120 parts of the made paper sheets and dried at 2.5 MPa and 60°C for 30 minutes to obtain flame retardant pressed kraft paper.
[0052] Example 3: A flame retardant pressed kraft paper, prepared by:
[0053] Step 1: Preparation of Oxidized Wood Pulp Fiber
[0054] By mass, the bleached coniferous wood pulp fiber was washed with ethanol and deionized water and dried to obtain pretreated wood pulp fiber, 7.1 parts of disodium hydrogen phosphate, 6 parts of sodium dihydrogen phosphate and 86.9 parts of deionized water were mixed to prepare a phosphate buffer, 100 parts of phosphate buffer, 1 part of pretreated wood pulp fiber, 0.04 parts of tetramethylpiperidine nitrogen oxide, and 1.73 parts of sodium chlorite were mixed evenly, and reacted at 60°C and 60rpm for 10 minutes. After the reaction was completed, 1 part of sodium hypochlorite was added to the reaction system, and the reaction was carried out at 60°C for 12 hours. After the reaction was completed, 4.5 parts of ethanol were added to terminate the reaction, the fiber was taken out, and washed with ethanol to obtain oxidized wood pulp fiber.
[0055] Step 2: Prepare flame retardant wood pulp fibers
[0056] By mass, 1 part of aluminum chloride and 9 parts of deionized water were mixed and stirred evenly to obtain an aluminum chloride solution. 2 parts of oxidized wood pulp fiber, 40 parts of ethanol and 20 parts of aluminum chloride solution were mixed and reacted at 70°C for 2 hours. After the reaction was completed, the fiber was taken out, washed with deionized water and dried at 60°C to obtain flame retardant wood pulp fiber.
[0057] Step 3: Preparation of magnesium-aluminum hydrotalcite matrix
[0058] By mass, 10 parts of ammonium carbonate and 100 parts of deionized water were mixed and stirred to obtain an ammonium carbonate solution; 17 parts of aluminum nitrate nonahydrate, 14 parts of magnesium nitrate hexahydrate, and 100 parts of deionized water were mixed and stirred to obtain an ammonium carbonate solution; the mixture was heated to 70°C, 110 parts of ammonium carbonate solution were added to the reaction system, and the mixture was reacted at 70°C and 60rpm for 2h. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried at 90°C for 12h to obtain a magnesium-aluminum hydrotalcite matrix.
[0059] Step 4: Prepare the flame retardant filler
[0060] 9.8 parts of phosphoric acid were added into the reactor by mass, and the phosphoric acid was stirred and heated at 30 rpm and a heating rate of 2-3°C / min, and the temperature was raised to 70°C. 10.8 parts of urea were added to the phosphoric acid, and the temperature was continued to be raised to 130°C, and 2 parts of magnesium aluminum hydrotalcite matrix were added, and the temperature was kept at 130°C for 20 minutes, and the temperature was raised to 170°C, cured for 2 hours, cooled, and crushed to obtain a flame retardant filler.
[0061] Step 5: Preparation of boric acid modified silica sol
[0062] By mass, 10 parts of tetraethyl orthosilicate and 150 parts of ethanol were mixed and stirred to obtain tetraethyl orthosilicate alcohol solution, 2 parts of boric acid were added to 160 parts of tetraethyl orthosilicate alcohol solution, and the pH of the solution was adjusted to 2 with hydrochloric acid, and the reaction was carried out at 70°C and 100rpm for 3h, and the temperature was raised to 80°C and the reaction was continued for 1h to obtain boric acid-modified silica sol.
[0063] Step 6: Prepare flame retardant laminated kraft paper
[0064] By weight, 12 parts of flame retardant wood pulp fibers and 40 parts of bleached coniferous wood pulp fibers were mixed and soaked in 500 parts of deionized water for 6 hours. The soaked mixed wood pulp fibers and 3000 parts of deionized water were added to a pulper for thorough pulping for 1 hour to obtain wood pulp slurry. The wood pulp slurry was deflated by a fiber separator at a deflation speed of 1000 rpm for 10 minutes to obtain deflated wood pulp slurry. 52 parts of the deflated wood pulp slurry, 1.2 parts of CPAM retention aid, and 5.2 parts of flame retardant filler were mixed and stirred evenly. The paper sheets were made by a sheeter. 30 parts of boric acid-modified silica sol were coated on 120 parts of the made paper sheets, and the paper sheets were dried at 2.5 MPa and 60°C for 30 minutes to obtain flame retardant pressed kraft paper.
[0065] Based on Example 1, control experiments were carried out, specifically Comparative Example 1, Comparative Example 2 and Comparative Example 3, as described below:
[0066] Comparative Example 1: No flame retardant wood pulp was added to the cellulose pulp, and other conditions were the same as those in Example 1.
[0067] A flame retardant pressed kraft paper, the preparation method is:
[0068] Step 1: Preparation of magnesium-aluminum hydrotalcite matrix
[0069] By mass, 10 parts of ammonium carbonate and 100 parts of deionized water were mixed and stirred to obtain an ammonium carbonate solution; 17 parts of aluminum nitrate nonahydrate, 14 parts of magnesium nitrate hexahydrate, and 100 parts of deionized water were mixed and stirred to obtain an ammonium carbonate solution; the mixture was heated to 70°C, 110 parts of ammonium carbonate solution were added to the reaction system, and the mixture was reacted at 70°C and 60rpm for 2h. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried at 90°C for 12h to obtain a magnesium-aluminum hydrotalcite matrix.
[0070] Step 2: Prepare flame retardant filler
[0071] 9.8 parts of phosphoric acid were added into the reactor by mass, and the phosphoric acid was stirred and heated at 30 rpm and a heating rate of 2-3°C / min, and the temperature was raised to 70°C. 10.8 parts of urea were added to the phosphoric acid, and the temperature was continued to be raised to 130°C, and 2 parts of magnesium aluminum hydrotalcite matrix were added, and the temperature was kept at 130°C for 20 minutes, and the temperature was raised to 170°C, cured for 2 hours, cooled, and crushed to obtain a flame retardant filler.
[0072] Step 3: Preparation of boric acid modified silica sol
[0073] By mass, 10 parts of tetraethyl orthosilicate and 150 parts of ethanol were mixed and stirred to obtain tetraethyl orthosilicate alcohol solution, 2 parts of boric acid were added to 160 parts of tetraethyl orthosilicate alcohol solution, and the pH of the solution was adjusted to 2 with hydrochloric acid, and the reaction was carried out at 70°C and 100rpm for 3h, and the temperature was raised to 80°C and the reaction was continued for 1h to obtain boric acid-modified silica sol.
[0074] Step 4: Prepare flame retardant laminated kraft paper
[0075] By mass, 50 parts of bleached coniferous pulp fibers were soaked in 500 parts of deionized water for 6 hours, the soaked bleached coniferous pulp fibers and 3000 parts of deionized water were added to a pulper for thorough pulping for 1 hour to obtain wood pulp slurry, the wood pulp slurry was deflated by a fiber separator at a deflation speed of 1000 rpm for 10 minutes to obtain deflated wood pulp slurry, 50 parts of the deflated wood pulp slurry, 1 part of CPAM retention aid, and 5 parts of flame retardant filler were mixed and stirred evenly, and paper sheets were made by a sheeter, 60 parts of boric acid modified silica sol were coated on 120 parts of the made paper sheets, and dried at 2.5 MPa and 60°C for 30 minutes to obtain flame retardant pressed kraft paper.
[0076] Comparative Example 2: No flame retardant filler was added, and other conditions were the same as those in Example 1.
[0077] A flame retardant pressed kraft paper, the preparation method is:
[0078] Step 1: Preparation of Oxidized Wood Pulp Fiber
[0079] By mass, the bleached coniferous wood pulp fiber was washed with ethanol and deionized water and then dried to obtain pretreated wood pulp fiber, 7.1 parts of disodium hydrogen phosphate, 6 parts of sodium dihydrogen phosphate and 86.9 parts of deionized water were mixed to prepare a phosphate buffer, 100 parts of phosphate buffer, 1 part of pretreated wood pulp fiber, 0.04 parts of tetramethylpiperidine nitrogen oxide and 1.73 parts of sodium chlorite were mixed evenly, and reacted at 60°C and 60rpm for 10 minutes. After the reaction was completed, 1 part of sodium hypochlorite was added to the reaction system, and the reaction was carried out at 60°C for 12 hours. After the reaction was completed, 4.5 parts of ethanol were added to terminate the reaction, the fiber was taken out, and washed with ethanol to obtain oxidized wood pulp fiber.
[0080] Step 2: Prepare flame retardant wood pulp fibers
[0081] By mass, 1 part of aluminum chloride and 9 parts of deionized water were mixed and stirred evenly to obtain an aluminum chloride solution. 2 parts of oxidized wood pulp fiber, 40 parts of ethanol and 20 parts of aluminum chloride solution were mixed and reacted at 70°C for 2 hours. After the reaction was completed, the fiber was taken out, washed with deionized water and dried at 60°C to obtain flame retardant wood pulp fiber.
[0082] Step 3: Preparation of boric acid modified silica sol
[0083] By mass, 10 parts of tetraethyl orthosilicate and 150 parts of ethanol were mixed and stirred to obtain tetraethyl orthosilicate alcohol solution, 2 parts of boric acid were added to 160 parts of tetraethyl orthosilicate alcohol solution, and the pH of the solution was adjusted to 2 with hydrochloric acid, and the reaction was carried out at 70°C and 100rpm for 3h, and the temperature was raised to 80°C and the reaction was continued for 1h to obtain boric acid-modified silica sol.
[0084] Step 4: Prepare flame retardant laminated kraft paper
[0085] By weight, 10 parts of flame retardant wood pulp fibers and 40 parts of bleached coniferous wood pulp fibers were mixed and soaked in 500 parts of deionized water for 6 hours. The soaked mixed wood pulp fibers and 3000 parts of deionized water were added to a pulper for thorough pulping for 1 hour to obtain wood pulp slurry. The wood pulp slurry was deflated by a fiber separator at a deflation speed of 1000 rpm for 10 minutes to obtain deflated wood pulp slurry. 50 parts of the deflated wood pulp slurry and 1 part of CPAM retention aid were mixed and stirred evenly. The paper sheets were made by a sheeter. 60 parts of boric acid-modified silica sol were coated on 120 parts of the made paper sheets. The paper sheets were dried at 2.5 MPa and 60°C for 30 minutes to obtain flame retardant pressed kraft paper.
[0086] Comparative Example 3: Silica sol was applied, and other conditions were the same as those in Example 1.
[0087] A flame retardant pressed kraft paper, the preparation method is:
[0088] Step 1: Preparation of Oxidized Wood Pulp Fiber
[0089] By mass, the bleached coniferous wood pulp fiber was washed with ethanol and deionized water and then dried to obtain pretreated wood pulp fiber, 7.1 parts of disodium hydrogen phosphate, 6 parts of sodium dihydrogen phosphate and 86.9 parts of deionized water were mixed to prepare a phosphate buffer, 100 parts of phosphate buffer, 1 part of pretreated wood pulp fiber, 0.04 parts of tetramethylpiperidine nitrogen oxide and 1.73 parts of sodium chlorite were mixed evenly, and reacted at 60°C and 60rpm for 10 minutes. After the reaction was completed, 1 part of sodium hypochlorite was added to the reaction system, and the reaction was carried out at 60°C for 12 hours. After the reaction was completed, 4.5 parts of ethanol were added to terminate the reaction, the fiber was taken out, and washed with ethanol to obtain oxidized wood pulp fiber.
[0090] Step 2: Prepare flame retardant wood pulp fibers
[0091] By mass, 1 part of aluminum chloride and 9 parts of deionized water were mixed and stirred evenly to obtain an aluminum chloride solution. 2 parts of oxidized wood pulp fiber, 40 parts of ethanol and 20 parts of aluminum chloride solution were mixed and reacted at 70°C for 2 hours. After the reaction was completed, the fiber was taken out, washed with deionized water and dried at 60°C to obtain flame retardant wood pulp fiber.
[0092] Step 3: Preparation of magnesium-aluminum hydrotalcite matrix
[0093] By mass, 10 parts of ammonium carbonate and 100 parts of deionized water were mixed and stirred to obtain an ammonium carbonate solution; 17 parts of aluminum nitrate nonahydrate, 14 parts of magnesium nitrate hexahydrate, and 100 parts of deionized water were mixed and stirred to obtain an ammonium carbonate solution; the mixture was heated to 70°C, 110 parts of ammonium carbonate solution were added to the reaction system, and the mixture was reacted at 70°C and 60rpm for 2h. After the reaction was completed, the mixture was filtered, washed with deionized water, and dried at 90°C for 12h to obtain a magnesium-aluminum hydrotalcite matrix.
[0094] Step 4: Prepare the flame retardant filler
[0095] 9.8 parts of phosphoric acid were added into the reactor by mass, and the phosphoric acid was stirred and heated at 30 rpm and a heating rate of 2-3°C / min, and the temperature was raised to 70°C. 10.8 parts of urea were added to the phosphoric acid, and the temperature was continued to be raised to 130°C, and 2 parts of magnesium aluminum hydrotalcite matrix were added, and the temperature was kept at 130°C for 20 minutes, and the temperature was raised to 170°C, cured for 2 hours, cooled, and crushed to obtain a flame retardant filler.
[0096] Step 5: Preparation of boric acid modified silica sol
[0097] By mass, 10 parts of tetraethyl orthosilicate and 150 parts of ethanol were mixed and stirred evenly to obtain a tetraethyl orthosilicate alcohol solution, which was reacted at 70° C. and 100 rpm for 3 h, then heated to 80° C. and continued to react for 1 h to obtain a boric acid-modified silica sol.
[0098] Step 6: Prepare flame retardant laminated kraft paper
[0099] By weight, 10 parts of flame retardant wood pulp fibers and 40 parts of bleached coniferous wood pulp fibers were mixed and soaked in 500 parts of deionized water for 6 hours. The soaked mixed wood pulp fibers and 3000 parts of deionized water were added to a pulper for thorough pulping for 1 hour to obtain wood pulp slurry. The wood pulp slurry was deflated by a fiber separator at a deflation speed of 1000 rpm for 10 minutes to obtain deflated wood pulp slurry. 50 parts of the deflated wood pulp slurry, 1 part of CPAM retention aid, and 5 parts of flame retardant filler were mixed and stirred evenly. The paper sheets were made by a sheeter. 60 parts of silica sol were coated on 120 parts of the made paper sheets, and the paper sheets were dried at 2.5 MPa and 60°C for 30 minutes to obtain flame retardant pressed kraft paper.
[0100] Detection experiment:
[0101] Quantitative test: According to "Determination of Quantitative Weight of Paper and Paperboard" (GB / T 451.2-2002), the test is carried out using a standard balance. A special cutter is used to cut samples from flame-retardant laminated kraft paper. The sample size is 100mm×100mm. The mass of each sample is measured and the quantitative weight of each sample is calculated.
[0102] Flame retardancy test: According to the "Test Method for Combustion Performance of Flame Retardant Paper and Paperboard" (GB / T14656-2009), a combustion test is used to conduct the test. A special sample cutter is used to cut a sample on the flame retardant pressed kraft paper. The sample size is 210mm×70mm. The sample is fixed on the sample clamp, and the flame height of the Bunsen burner is adjusted to 40mm. The Bunsen burner is slid so that the flame of the Bunsen burner contacts the bottom edge of the sample for 12s, then the Bunsen burner is removed and the afterburning time, burning time and carbonization length of the sample are recorded.
[0103]
[0104] Conclusion: It can be seen from the experiment that the sample obtained by the preparation method of Example 1 is superior to the samples prepared by the preparation methods of Comparative Examples 1, 2 and 3 in the tooth replacement strength test and the flame retardancy test. The flame retardant pressed kraft paper prepared in Example 1 is superior to the flame retardant pressed kraft paper prepared by Comparative Examples 1, 2 and 3 in terms of ring compression strength, afterflaming time, burning time and carbonization length, and meets the performance indicators of flame retardant paper (afterflaming time ≤5s; burning time ≤60s; carbonization length ≤115mm), which effectively solves the problem that ordinary pressed kraft paper is flammable and not flame retardant enough.
[0105] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing flame retardant pressed kraft paper, characterized in that: The preparation method is: The flame retardant wood pulp fiber and the bleached coniferous wood pulp fiber are mixed, soaked and then beaten to obtain wood pulp slurry, the wood pulp slurry is dispersed and mixed with a retention aid and a flame retardant filler, stirred evenly, and paper sheets are obtained through papermaking, and boric acid-modified silica sol is coated on the paper sheets and dried to obtain flame retardant pressed kraft paper.
2. The method for preparing a flame retardant pressed kraft paper according to claim 1, characterized in that: The preparation method of flame retardant wood pulp fiber is: The bleached softwood pulp fiber is washed with ethanol and deionized water, and then dried to obtain pretreated pulp fiber, disodium hydrogen phosphate, sodium dihydrogen phosphate and deionized water are mixed to prepare a phosphate buffer, the phosphate buffer, the pretreated pulp fiber, tetramethylpiperidinium nitrogen oxide and sodium chlorite are evenly mixed, and the mixture is reacted at 55-65° C. and 50-70 rpm for 5-15 min, and after the reaction is completed, sodium hypochlorite is added to the reaction system, and the mixture is reacted at 55-65° C. and 50-70 rpm for 11-13 h, and after the reaction is completed, ethanol is added to terminate the reaction, and the fiber is taken out and washed with ethanol to obtain oxidized pulp fiber; Aluminum trichloride and deionized water are mixed and stirred evenly to obtain an aluminum trichloride solution. Oxidized wood pulp fiber, ethanol and aluminum trichloride solution are mixed and reacted at 65-75°C for 1-3 hours. After the reaction is completed, the fiber is taken out, washed with deionized water, and dried at 55-65°C to obtain flame-retardant wood pulp fiber.
3. The method for preparing a flame retardant pressed kraft paper according to claim 1, characterized in that: The preparation method of the flame retardant filler is: Mix ammonium carbonate and deionized water, stir evenly to obtain an ammonium carbonate solution, mix aluminum nitrate nonahydrate, magnesium nitrate hexahydrate, and deionized water, stir evenly, heat to 65-75° C., add the ammonium carbonate solution to the reaction system, react at 65-75° C. and 55-65 rpm for 1-3 hours, filter after the reaction, wash with deionized water, and dry at 85-95° C. for 10-14 hours to obtain a magnesium-aluminum hydrotalcite matrix; Phosphoric acid is added into a reactor, and the phosphoric acid is stirred and heated at 25-35 rpm and a heating rate of 2-4°C / min, and the temperature is raised to 65-75°C, urea is added into the phosphoric acid, and the temperature is further raised to 120-140°C, and a magnesium-aluminum hydrotalcite matrix is added into the phosphoric acid, and the temperature is kept at 120-140°C for 15-25 minutes, and the temperature is raised to 165-175°C, and the phosphoric acid is cured for 1.5-2.5 hours, cooled, and crushed to obtain a flame retardant filler.
4. The method for preparing a flame retardant pressed kraft paper according to claim 1, characterized in that: The preparation method of boric acid modified silica sol is: Mix tetraethyl orthosilicate and ethanol, stir evenly to obtain tetraethyl orthosilicate alcohol solution, add boric acid to the tetraethyl orthosilicate alcohol solution, and adjust the pH of the tetraethyl orthosilicate alcohol solution to 1-3 with hydrochloric acid, react at 65-75°C and 90-110rpm for 2-4h, heat to 75-85°C, continue to react for 0.5-1.5h, and obtain boric acid modified silica sol.
5. The method for preparing a flame retardant pressed kraft paper according to claim 1, characterized in that: The mass ratio of flame retardant wood pulp fiber to bleached coniferous wood pulp fiber is (0.8-1.2):(3.6-4.4).
6. The method for preparing a flame retardant pressed kraft paper according to claim 1, characterized in that: The mass ratio of wood pulp slurry to retention aid and flame retardant filler is (48-52):(0.8-1.2):(4.8-5.2).
7. The method for preparing a flame retardant pressed kraft paper according to claim 2, characterized in that: The oxidized wood pulp fiber raw material includes 95 to 115 parts of phosphate buffer, 0.8 to 1.2 parts of pretreated wood pulp fiber, 0.03 to 0.05 parts of tetramethylpiperidinium nitrogen oxide, 1.72 to 1.74 parts of sodium chlorite, and 0.8 to 1.2 parts of sodium hypochlorite, in parts by mass.
8. The method for preparing a flame retardant pressed kraft paper according to claim 2, characterized in that: The mass ratio of oxidized wood pulp fiber, ethanol and aluminum chloride solution is (1.8-2.2):(35-45):(18-22).
9. The method for preparing a flame retardant pressed kraft paper according to claim 3, characterized in that: The mass ratio of phosphoric acid, urea and magnesium aluminum hydrotalcite matrix is (9.6-10.0):(10.6-11.0):(1.5-2.5).
Citation Information
Patent Citations
Composite flame-retardant filler and flame-retardant paper added with flame-retardant filler
CN103806331A
Preparation method of modified acrylate pressure sensitive adhesive
CN108342173A
Flame retardant kraft box paperboard and preparation method thereof
CN109355967A
Flame-retardant anti-ultraviolet fiber
CN117127394A